2020
DOI: 10.1055/s-0039-3399395
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Health Anxiety in Neurology and Psychiatry Settings

Abstract: Objectives Prevalence of health anxiety is highly varied based on different settings and samples studied. This study aimed to assess the prevalence of health anxiety among outpatients attending neurology and psychiatry outpatient setting in tertiary care hospital and understand the clinical correlates. Participants and Methods This was a cross-sectional study conducted in the outpatient settings including participants fulfilling study criteria. The assessments included semi-structured proforma for demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…An Indian study reported the occurrence of health anxiety as 25% and 19% in psychiatry and neurology settings, and in both scenarios, patients with somatoform disorder and multiple diagnoses had high health anxiety. [ 13 ] Health anxiety has been identified as a risk factor for the onset of panic disorder. [ 1 ] Panic disorder also has higher rates of health anxiety compared to other anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…An Indian study reported the occurrence of health anxiety as 25% and 19% in psychiatry and neurology settings, and in both scenarios, patients with somatoform disorder and multiple diagnoses had high health anxiety. [ 13 ] Health anxiety has been identified as a risk factor for the onset of panic disorder. [ 1 ] Panic disorder also has higher rates of health anxiety compared to other anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…As the predictive value is related to disease prevalence, estimates of predictive values for a range of estimated prevalence rates were modelled. These were 1, 2 and 4%, which relates to the prevalence of clinically significant health anxiety in the general population [ 42 ], 20% in medical clinics [ 43 ] and 25% to psychiatry outpatient settings [ 44 ].…”
Section: Methodsmentioning
confidence: 99%